International Law, Human Rights and Realpolitik: The Case of Cyprus - Tassou, Thalia; Constantinides, Stephanos (Études helléniques / Hellenic Studies, 2002)
Human rights have become the new dominant ideology in international relations. In this article, taking as an example the case of Cyprus, we try to show that the policy of human rights is applied in a selective manner which takes into consideration the interests of the Western world – the United States playing a leading role – more than the general principles of justice. It is evident that this question is vast and consequently we limit ourselves to certain aspects in order to show that the ideology of human rights, in itself of an unquestionable ethical value, is in reality serving the interests of the rich and developed countries which manipulate it accordingly.